Quantitative reanalysis of aggregate data on IQ in sexual offenders. [article]. - Cantor, J.M.
General intelligence has been the most commonly studied neuropsychological characteristic of sexual offenders for over 70 years. Results, however, have been highly inconsistent. To assess whether sexual offenders score lower in IQ than nonsexual offenders and to explore which sexual offense characteristics relate to IQ, the authors reanalyzed all reports providing sufficient information. Data spanned 236 samples, comprising 25,146 sexual offenders and controls. The literature contained sufficient information to permit comparison of adult versus juvenile sexual offenders, offenders targeting children versus adults, offenders targeting their own versus unrelated children, and offenders targeting boys versus girls. Results confirm the association between IQ and sexual offending and suggest that previous discrepancies are attributable to how many pedophilic individuals were in each sample. -- (from the author)